PERAN KUALITAS AUDIT DAN DETEKSI FRAUDULENT FINANCIAL STATEMENT BERBASIS FRAUD PENTAGON PADA BADAN USAHA MILIK NEGARA - Daeli, Yata fati Elli (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
Fraud is a phenomenon of fraud that can still occur in a company which usually begins with an opportunity to indicate irregularities. Fraud that occurs in the business world cannot be denied that it can occur when a company cannot carry out effective supervision in the process of running its business. This study aims to detect indications of fraudulent financial statements using the fraud pentagon model with audit quality as a moderating variable. The sample used is 16 state-owned companies listed on the Indonesia Stock Exchange for the period 2015-2019. The data used is secondary data obtained from the company website and the Indonesia Stock Exchange web page. The data analysis method uses descriptive analysis and analysis with the SEM-PLS (Structural Equation Modeling-Partial Least Square) method, where processing is assisted by Microsoft Excel 2016 and WarpPLS 6.0 software. The results of this study indicate that the opportunity and competence variables are proven to have a significant effect on the detection of fraudulent financial statements. Meanwhile, pressure, rationalization, and arrogance variables were not proven to have a significant effect on fraudulent financial statement detection. The role of audit quality is proven to be able to moderate the influence of the rationalization and competence variables on the detection of fraudulent financial statements. However, the role of audit quality was not proven to be able to moderate the influence of the pressure, opportunity and arrogance variables on the detection of fraudulent financial statements.Keywords: Fraudulent financial statement, fraud pentagon, audit quality.